2006
DOI: 10.1159/000090215
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Cholesterol 24S-Hydroxylase Gene (CYP46A1) Associated with the APOEυ3 Allele Increases the Risk of Alzheimer’s Disease and of Mild Cognitive Impairment Progressing to Alzheimer’s Disease

Abstract: Background: Late-onset Alzheimer’s disease (LOAD) is associated with changes in certain proteins, such as ApoE and Cyp46A1, of the elimination route for cerebral cholesterol. The main lipoprotein involved in its transport is ApoE whose υ4 allele is the least efficient. However, the presence or absence of this allele does not determine the development of LOAD, which implies the existence of other susceptibility factors associated with the disease, such as the CYP46A1 gene that encodes the enzyme cholesterol 24S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Such a discrepancy is often found in case of selection bias and regional differences in the population structure. The genotype frequency distribution of our data set fell in the range [12,13,[22][23][24] , and represented a sample size similar to those of other studies. However, the inconsistence in association analyses between the current result and those in previous reports need further clarification.…”
Section: Discussionsupporting
confidence: 65%
“…Such a discrepancy is often found in case of selection bias and regional differences in the population structure. The genotype frequency distribution of our data set fell in the range [12,13,[22][23][24] , and represented a sample size similar to those of other studies. However, the inconsistence in association analyses between the current result and those in previous reports need further clarification.…”
Section: Discussionsupporting
confidence: 65%
“…In the periphery, systemic cholesterol is metabolized within the body to one of a number of products including the metabolite 27-hydroxycholesterol which can cross the BBB and enter the CNS (Heverin et al ., 2005). The role of cholesterol metabolites in learning and memory in humans have been explored by measuring levels of 24S- and 27-hydoxycholesterol in serum and the cerebrospinal fluid (Kolsch et al ., 2004; Papassotiropoulos et al ., 2002; van den Kommer et al ., 2009) and by identifying genetic polymorphisms related to cognitive impairment and Alzheimer’s disease (Fernandez del Pozo et al ., 2006; Fu et al ., 2009; Papassotiropoulos et al ., 2005). Animal studies of the effects of cholesterol metabolites on learning and memory have included knockout mice lacking 24-hydroxylase (Kotti et al ., 2006), infusion of 24-hydroxycholesterol into the brain (Zhao et al ., 2009) and manipulation of the CYP46A1 gene that encodes the enzyme cholesterol 24-hydroxylase (Hudry et al ., 2009).…”
Section: Cholesterol Metabolitesmentioning
confidence: 99%
“…Papassotiropoulos et al (2005) reported that a cluster of cholesterol-related genes including a single nucleotide polymorphism of CYP46A1 (rs754203) contributed to the risk for Alzheimer’s disease. Fernandez del Pozo and her colleagues examined the effect of the polymorphic site rs754203 on mild cognitive impairment and Alzheimer’s disease in patients with the ApoE3 or ApoE4 allele (Fernandez del Pozo et al ., 2006). They found that the polymorphism increased the risk of Alzheimer’s disease in those with the ApoE3 form but not in those with the ApoE4 form.…”
Section: Cholesterol Metabolitesmentioning
confidence: 99%
“…In studies of the relationship between CYP46A1 gene polymorphism and AD risk, a single nucleotide polymorphism (SNP) T/C in the region rs754203 of the CYP46A1 gene has been identified, and a significant correlation with an increased risk for AD has been revealed. According to these studies, the frequency of both the CYP46A1 TT-homozygotes genotype and the T allele was significantly higher in AD patients than in controls (15)(16)(17). Conversely, other studies reported that the CChomozygotes genotype was observed more frequently in AD patients than in the control subjects (18)(19)(20).…”
Section: Introductionmentioning
confidence: 93%